Implementation of Environmental Management Systems in the Slovak Republic - Majernik, Milan; Chovancova, Jana (Communications - Scientific letters of the University of Zilina, 2010)
The human environment is always influenced by enterprise activity, which is mostly negative. The introduction of an Environmental Management System (EMS) can be an important step towards fulfilling the principles of sustainable development on a practical level. However, there are few ways of EMS implementation. Authors of the paper present and analyze possible approaches of EMS implementation in Slovak enterprises. According to this analysis possible development trends in the environmental management can be indicated.